Cultural content in the digital arena: toward the hybridization of legal and business models - Maggiolino, Mariateresa; Montagnani, Maria; Nuccio, Massimiliano (Organizational Aesthetics, 2014)
Literature on online piracy has focused mainly on the legal framework necessary to prevent and punish copyright infringements on both the demand and supply sides. More recently, marketing and psychology studies have tried to understand the behavioral and ethical aspects connected with the consumption of pirated digital goods but little attention has been dedicated to the evolution in the distribution of digital content. This paper will analyze digital business models, isolate the main forms of digital distribution and evaluate the degree of hybridization that these businesses have accomplished in the move away from the traditional brick-and-mortar model. The article presents the results of an empirical study of 597 websites which distribute digital media content. For each website, data have been collected on a range of features including the distribution methods, the technical restrictions imposed on content, the copyright management and licensing systems, and the revenue models adopted. Using a non-linear cluster technique, the data collected reveal unexpected characteristics in the current landscape for online distribution. While it is commonly assumed that the current legislative framework tends to incentivize a system based on strong legal and technological control over content, the cluster analysis reveals that legal factors are not the most relevant ones in shaping a landscape which is mostly determined by technology and organizational solutions. The authors conclude by offering hybridization policies as a possible strategic development for fighting online piracy.